Clinically relevant radiographic progression in joint destruction in RA patients with abnormal MMP-3 or high levels of CRP despite 1-year treatment with infliximab. Issue 6 (1st November 2016) - Nawata, Masao; Saito, Kazuyoshi; Fukuyo, Shunsuke; Hirata, Shintaro; Tanaka, Yoshiya
Abstract: Objective : Identify the independently related factors of joint destruction progression in RA patients despite of infliximab treatment. Methods : The subjects were cases who underwent infliximab treatment for one year or longer in our department ( n  = 244). Patients in which modified total sharp score (mTSS), joint erosion (JE), and joint space narrowing (JSN) had advanced to the standard value (3.0) or more for one year were defined as mTSS- Clinically-Relevant-Rapid Progression (CRRP) ( n  = 20), JE-CRRP ( n  = 20), and JSN-CRRP ( n  = 23), and the respective related factors at baseline and week 54 were defined by multiple logistic regression. Results : The median disease duration was 24 months and median mTSS 9.0 at baseline. The median DAS28, CRP, and yearly progression of mTSS improved from 5.8 to 2.6, 1.2 to 0.1 mg/dL, and 4.4 to 0.0 point/year, respectively. The related factor in each of mTSS-CRRP, JE-CRRP, and JSN-CRRP was high CRP levels at baseline. At week 54, the related factor of mTSS-CRRP and JSN-CRRP was high MMP-3 titer; however, the related factor of JE-CRRP was high CRP levels. Conclusion : High CRP levels at baseline were an independent predictive factor of joint destruction advancement during infliximab treatment. Moreover, it was believed that abnormal MMP-3 at week 54 was the index for mTSS and JSN advancement, while high CRP levels were the index for JE advancement.